Ending Africa's energy deficit and the law : achieving sustainable energy for all in Africa - Omorogbe, Yinka; Ordor, Ada Okoye (Oxford : Oxford University Press, 2018)
With the inclusion of access to energy in the sustainable development goals, the role of energy to human existence was finally recognized. Yet, in Africa, this achievement is far from realized. Omorogbe and Ordor bring together experts in their fields to ask what is stalling progress, examining problems from institutions catering to vested interests at the continent's expense, to a need to develop vigorous financial and fiscal frameworks. The ramifications and complications of energy law are labyrinthine: this volume discusses how energy deficits can burden disabled people, women, and children in excess of their more fortunate counterparts, as well as considering environmental issues, including the delicate balance between the necessity of water for drinking and cleaning and the use of water in industrial processes.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 5, 2018).
Keywords: Power resources -- Africa; Sustainable development -- Africa; Power resources -- Law and legislation -- Africa; Environment and Ecology; The environment